Exploring Academic Challenges In Arabic Linguistics Learning: Cognitive, Linguistic, And Pedagocical Perspectives In Indonesian Islamic Higher Education/ التحديات الأكاديمية في تعليم اللسانيات العربية: من منظور الجانب المعرفي واللغوي والتربوي في التعليمِ الجامعي الإسلامي بإندونيسيا - Muhammad Afifudin Dimyathi; Muzakki Abdurrahman; Muhammad Al-Mubassyir; Achmad Yani; Shofil Fikri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Arabic linguistics is a core course in Arabic Language and Arabic Language Education programs at higher education institutions, and despite its crucial role as a theoretical foundation for linguistic studies, it is often perceived by students as abstract, complex, and highly demanding in terms of analytical skills. This study aims to identify and analyze the academic challenges faced by undergraduate and postgraduate students in learning Arabic linguistics at Islamic higher education institutions. Employing a mixed-methods approach with an explanatory sequential design, the study involved the distribution of Likert-scale questionnaires to 120 students and semi-structured interviews with selected informants at UIN Sunan Ampel Surabaya. The findings indicate that students’ academic challenges encompass cognitive, linguistic, and pedagogical aspects, with cognitive challenges emerging as the dominant factor, particularly in relation to difficulties in understanding abstract linguistic concepts and the high cognitive load involved. Linguistic challenges are associated with the complexity of terminology and the morphosyntactic structure of the Arabic language, while pedagogical challenges relate to instructional approaches that remain predominantly theoretical and lecturer-centered. The study also reveals differences in the characteristics of challenges between undergraduate and postgraduate students in terms of both difficulty levels and the linguistic areas perceived as most challenging, leading to the recommendation that Arabic linguistics instruction in higher education be developed in a more contextualized, analytical, and tiered manner.